MANAJEMEN PRODUKSI DAN PENENTUAN HARGA POKOK PRODUKSI (HPP) PADA BERBAGAI TIPE PETERNAK AYAM BROILER - Novi Kurniawati; Hanung Ismono; Wuryaningsih Dwi Sayekti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aims  to analyze: the management of the broiler chicken poultry production of independent supervision, semi-independent and partnership, the cost of goods broiler production independent supervision, semi-independent and partnership in Purwoasri Village North Metro District Metro City and in Kedaton 2 Village Batang Hari Nuban District regency of East Lampung. This research was conducted in October until November 2013. Primary and secondary data were collected in this reserch. The amount of research respondents were three people, who were an independent poultry, semi-independent and partnership. The methods of data analysis used in this research was descriptive, qualitative and quantitative analysis. The results showed that (1) the management of the broiler chicken production with the supervision of partnership was the best with scores 132 higher than the semi-independent and independent supervision. Some of excellence management production partnership supervision were the application of the cleaning system equipment enclosure, transportation of DOC, admission of DOC process to the cage, preservation of the cage, giving the woof and handling of harvest item (2) the highest cost of goods production per kilogram of broiler chicken was the poultry with partnership supervision Rp13,531.00/kg, whereas the poultry with independent supervision was Rp13,496.36 and the poultry with semi-independent supervision was Rp13,109.67/kg. Keywords: Broiler chicken, HPP, poultry, production management